Obesity under the moonlight of c-MYC - Nevzorova, Yulia A.; Cubero, Francisco Javier (Frontiers in Cell and Developmental Biology, 2023)
The moonlighting protein c-Myc is a master regulator of multiple biological processes including cell proliferation, differentiation, angiogenesis, apoptosis and metabolism. It is constitutively and aberrantly expressed in more than 70% of human cancers. Overwhelming evidence suggests that c-Myc dysregulation is involved in several inflammatory, autoimmune, metabolic and other non-cancerous diseases. In this review, we addressed the role of c-Myc in obesity. Obesity is a systemic disease, accompanied by multi-organ dysfunction apart from white adipose tissue (WAT), such as the liver, the pancreas, and the intestine. c-Myc plays a big diversity of functions regulating cellular proliferation, the maturation of progenitor cells, fatty acids (FAs) metabolism, and extracellular matrix (ECM) remodeling. Moreover, c-Myc drives the expression of a wide range of metabolic genes, modulates the inflammatory response, induces insulin resistance (IR), and contributes to the regulation of intestinal dysbiosis. Altogether, c-Myc is an interesting diagnostic tool and/or therapeutic target in order to mitigate obesity and its consequences.